2017
DOI: 10.1002/dc.23853
|View full text |Cite
|
Sign up to set email alerts
|

Primary diagnosis of angiosarcoma by fine needle aspiration: Lessons learned from 3 cases

Abstract: Angiosarcomas are rare malignancies arising from cells of endothelial origin and are aggressive sarcomas that can occur in any anatomic site. They are reported to have predilection for the scalp, extremities and breasts. The incidence of these tumors is increasing, which has been suggested to be attributable to the growing use of radiotherapy to treat breast and other malignancies. There is currently limited literature describing the primary cytologic diagnosis of angiosarcoma on fine needle aspirate material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The authors observed large polygonal cells with vacuolated cytoplasm, harboring round eccentrically located nuclei with prominent nucleolus, arranged in small clusters or dispersed. Other reports in addition to these features refer to specific characteristics, such as the presence of intracytoplasmic lumina, containing red blood cells (erythrophagocytosis) or neutrophils [6][7][8]. However, the diagnosis of TAS by FNA is still challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed large polygonal cells with vacuolated cytoplasm, harboring round eccentrically located nuclei with prominent nucleolus, arranged in small clusters or dispersed. Other reports in addition to these features refer to specific characteristics, such as the presence of intracytoplasmic lumina, containing red blood cells (erythrophagocytosis) or neutrophils [6][7][8]. However, the diagnosis of TAS by FNA is still challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In one of these cases, the spindle-to-epithelioid, highly atypical dispersed cells raised the possibility of sarcoma. Identification of the correct histiotype was based on the combination of cytomor- phology with a panel of immunostains including endothelial markers [8,10]. It is generally accepted that the cytological features are not definitively diagnostic [2].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, on cytology smears, cutaneous angiosarcoma is difficult to recognize due to its heterogeneous cytologic features and overlap with carcinomas, cutaneous adnexal tumors, malignant melanoma and epithelioid soft tissue neoplasms. Due to its rarity, only a few case reports and small series are available in the literature 3‐11 5 or intracytoplasmic hemosiderin deposits 4 are diagnostic clues, but vaso‐formative features like intracytoplasmic vacuoles containing red blood cells, microacinar “lumen” formation, hemophagocytosis and vascular channels are neither present in all cases, nor pathognomonic for angiosarcoma 3,5,7 .…”
Section: Figurementioning
confidence: 99%
“…49 An equal option in patients with BRAF V600E mutations is the targeted therapy with a BRAF inhibitor (vemurafenib, dabrafenib, encorafenib) alone or in combination with a MEK inhibitor (cobimetinib, trametinib, or binimetinib, respectively). A combination of a BRAF and a MEK inhibitor is indicated in cases of (i) patients with BRAF-mutated tumors that do not respond to immunotherapy, (ii) rapidly growing BRAF-mutated tumors, since the response of BRAF/MEK inhibition is immediate, contrary to immunotherapy, and (iii) for patients unable to tolerate or benefit from immunotherapy, such as older patients with major comorbid conditions, the presence of underlying immunodeficiency 18,43 Atypical spindle to epithelioid cells with abundant cytoplasm VIII-related antigen, CD31 Malignant melanoma with wide hemorrhage areas PEComa 17 Clear glycogen-rich cytoplasm, small centrally placed nucleoli S-100, HMB-45 Epithelioid and spindled cells arranged perivascularly Angiomyolipoma 44 Admixture disease, or those undergoing chronic immunosuppression for rheumatologic diseases or organ transplantation. 49 Therefore, when quick response is needed, targeted therapy is preferred.…”
Section: Therapeutic Approachmentioning
confidence: 99%